Disinfection by-products from halogenation of aqueous solutions of terpenoids - Joll, Cynthia; Alessandrino, Michael; Heitz, Anna (Elsevier Science Ltd, 2010)
We report the formation of trihalomethanes and other disinfection by-products from four polyfunctional terpenoids during simulated chlorination of natural waters. Complex suites of products were identified by closed loop stripping analysis (CLSA)/gas chromatography-mass spectrometry (GC-MS) from halogenation of b-carotene and retinol. b-Ionone appeared to be a key intermediate in the halogenation of b-carotene and retinol, reacting further under the reaction conditions to produce trans-b-ionone-5,6-epoxide and b-cyclocitral. Halogenation of the four terpenoids also produced trihalomethanes (THMs), most likely through haloform reaction on methyl ketone groups within many of the intermediates. Since halogenation of retinol produced a significant quantity of THMs at a slow reaction rate, retinol-based structures may possibly contribute to the slow reacting phase of THM formation in natural waters. Two polyhydroxyphenol model compounds were halogenated for comparison. The only products identified by CLSA/GC-MS from halogenation of 40,5,7- trihydroxyflavanone and ellagic acid were THMs. 40,5,7-Trihydroxyflavanone rapidly produced THMs, with an extremely high molar yield (94%) at pH 7. Terpenoids of the b-ionone and retinol type should be considered to be significant THM precursors, while 40,5,7-trihydroxyflavanone has been shown to be an extremely significant THM precursor, potentially present within natural organic matter in water treatment processes and distribution systems